Medium-Term Outcomes of COVID-19 Infection After Kidney Transplantation for Ongoing Living and Deceased Kidney Transplantations within the COVID-19 Pandemic - Simforoosh, Naser; Eslami, Atefe; Mohammadian Roshan, Yaghub; Ali Askari, Majeed; Masoumi, Navid; Vaezjalali, Maryam; Ziaeefar, Pardis; Kashi, Amir Hossein (Urology Journal, 2022)
Objectives: To present the early to midterm experience of two referral kidney transplantation centers with living and deceased kidney transplantations that were performed within the COVID-19 pandemic. Materials and Methods: All cases performed in two referral centers in Iran within the COVID-19 pandemic were investigated. Transplantations were performed from May 2020 to February 2021. The protocol for screening included nasopharyngeal RT-PCR with chest CT scan for living and deceased transplantations in center A and RTPCR for living transplantations and chest CT scan for deceased transplantations in center B. Patients were followed for 14-26 months after transplantation regarding COVID-19 infection and its outcomes in case of infection. Results: 103 kidney transplantations were performed during the study period including 54 (52.4%) living and 49 (47.6%) deceased kidney transplantations. Twenty-four recipients (23.3%) and a living donor (1%) were infected with COVID-19. The severity of COVID-19 infection was mild, moderate, severe, and critical in 16 (66.6%), 4 (16.6%), 2 (8.4%), and 2 patients (8.4%), respectively. Two mortalities were observed within transplantation recipients with COVID-19 infection (1.9%). 87.5% (7/8) COVID-19 infections in center B were observed in recipients of deceased transplantations who were screened only by chest CT scan. Conclusion: The results of this study indicate a low frequency of COVID-19 mortality (1.9% for the whole cohort and 8.3% within COVID-19 infected patients) for recipients of living and deceased kidney transplantation that were performed within the COVID-19 pandemic. The above findings highlight for the first time in a large study the probability of living kidney transplantation during the COVID-19 pandemic in case strict screening of donors and recipients and close supervision of operating rooms and wards are implemented. We further hypothesize the inadequacy of chest CT scan for screening of COVID-19 in kidney transplantation surgery candidates.